Troponin T, N-terminal pro-B-type natriuretic peptide, and incidence of stroke: The atherosclerosis risk in communities study - Folsom, A.; Nambi, V.; Bell, E.; Oluleye, O.; Gottesman, R.; Lutsey, P.; Huxley, Rachel; Ballantyne, C. (2013)
Background and Purpose-Increased levels of plasma troponins and natriuretic peptides are associated with increased risk of cardiovascular disease, but only limited information exists on these biomarkers and stroke occurrence. In a prospective epidemiological study, we tested the hypothesis that high-sensitivity troponin T (TnT) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) are associated positively with incidence of stroke. Methods-The Atherosclerosis Risk in Communities (ARIC) Study measured plasma TnT and NT-proBNP in 10 902 men or women initially free of stroke and followed them for a mean of 11.3 years for stroke occurrence (n=507). Results-Both biomarkers were associated positively with total stroke, nonlacunar ischemic, and especially cardioembolic stroke, but not with lacunar or hemorrhagic stroke. For example, after adjustment for prevalent risk factors and cardiac diseases, the hazard ratios (95% CIs) for jointly high values of TnT and NT-proBNP (versus neither biomarker high) were 2.70 (1.92-3.79) for total stroke and 6.26 (3.40-11.5) for cardioembolic stroke. Associations with stroke appeared somewhat stronger for NT-proBNP than TnT. Strikingly, ˜58% of cardioembolic strokes occurred in the highest quintile of prestroke NT-proBNP, and 32% of cardioembolic strokes occurred in participants who had both NT-proBNP in the highest quintile and were known by ARIC to have atrial fibrillation sometime before their cardioembolic stroke occurrence. Conclusions-In the general population, elevated plasma TnT and NT-proBNP concentrations are associated with increased risk of cardioembolic and other nonlacunar ischemic strokes. © 2013 American Heart Association, Inc.